HAVING GOOD SPEAKING THROUGH BRITISH PARLIAMENTARY SYSTEM DEBATE - Megawati Basri; Martika Kudani; Jasmal Martora (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasifik Morotai, 2023)
This research was conducted to see if there was a development in speaking skill after applying the debate technique ( British parliamentary system) to the students at Universitas Pasifik Morotai. The researcher was used quantitative research as the method. The samples of the research were 32 students which consist of 1st and 3rd years English The research was used pre-experimental and used one-group pre-test post-test design ; purposive sampling to get the sample. Based on the findings showed that the mean in pre-test were 12.22 and the mean of the post-test were 13.03 it means that debate technique can improve students speaking skill at Universitas Pasifik Morotai.